1996
DOI: 10.1302/0301-620x.78b2.0780258
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Diagnosis of Bone Tumours

Abstract: We evaluated the diagnostic accuracy of fine-needle aspiration biopsy in a prospective study of 300 patients with previously undiagnosed bone lesions. Patients with suspected local recurrence of a primary bone tumour or a metastatic lesion of a previously diagnosed malignancy were excluded. Fine-needle aspiration biopsy was performed under radiological control as an outpatient procedure.The series was grouped into three major categories: 1) benign bone lesions including infections; 2) primary malignant bone tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 18 publications
5
61
1
1
Order By: Relevance
“…In a study of 300 patients, we reported correct discrimination between benign, primary malignant and secondary malignant bone lesions in 95% of adequate fine-needle aspirates. 4 Similar figures were found by Bommer, Ramzy and Mody 5 in a study of 427 patients with skeletal lesions. Ruhs, El-Khoury and Chrischilles 6 found FNAB to be more cost-effective than open biopsy.…”
supporting
confidence: 80%
“…In a study of 300 patients, we reported correct discrimination between benign, primary malignant and secondary malignant bone lesions in 95% of adequate fine-needle aspirates. 4 Similar figures were found by Bommer, Ramzy and Mody 5 in a study of 427 patients with skeletal lesions. Ruhs, El-Khoury and Chrischilles 6 found FNAB to be more cost-effective than open biopsy.…”
supporting
confidence: 80%
“…The accuracy of core-needle biopsy in terms of correct histologic features in another combined series (2) of soft-tissue and bone tumors was 84% (52 of 62). Some authors (2,3) have suggested that core-needle biopsy may be more effective for evaluation of primary tumors of bone than for evaluation of tumors of the soft tissue. In one early series (4), however, the success rate of large-gauge trephine core biopsy of 16 primary bone tumors was only 44%.…”
mentioning
confidence: 99%
“…This fast, nontraumatic, outpatient procedure has during the last 20 years been utilized in both soft-and bone lesions. The reliable results in clinical practice have been shown in several studies (Kreicbergs et al 1996, Åkerman 1997, Wedin et al 2000. FNAB is generally accepted at most Scandinavian centers for the diagnosis of soft tissue tumors.…”
Section: Fine Needle Aspiration Biopsy (Fnab)mentioning
confidence: 79%